3(2n-2)=5(n+3)

Simple and best practice solution for 3(2n-2)=5(n+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2n-2)=5(n+3) equation:


Simplifying
3(2n + -2) = 5(n + 3)

Reorder the terms:
3(-2 + 2n) = 5(n + 3)
(-2 * 3 + 2n * 3) = 5(n + 3)
(-6 + 6n) = 5(n + 3)

Reorder the terms:
-6 + 6n = 5(3 + n)
-6 + 6n = (3 * 5 + n * 5)
-6 + 6n = (15 + 5n)

Solving
-6 + 6n = 15 + 5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5n' to each side of the equation.
-6 + 6n + -5n = 15 + 5n + -5n

Combine like terms: 6n + -5n = 1n
-6 + 1n = 15 + 5n + -5n

Combine like terms: 5n + -5n = 0
-6 + 1n = 15 + 0
-6 + 1n = 15

Add '6' to each side of the equation.
-6 + 6 + 1n = 15 + 6

Combine like terms: -6 + 6 = 0
0 + 1n = 15 + 6
1n = 15 + 6

Combine like terms: 15 + 6 = 21
1n = 21

Divide each side by '1'.
n = 21

Simplifying
n = 21

See similar equations:

| (x+1)+5=7 | | 2x+9=5x+12 | | 300w7500+850w | | 4x-12=2x+7 | | (3x-1)^2=75 | | (3/x+2)+(2/x-6)= | | -2x^2+4x+9=0 | | 6+-12 | | 625625dividedbyTim | | X | | (3x+2)(2x^2-15x+18)=0 | | 6,2-30+4,4-x=2013 | | 2x+4=n+7 | | (10x-3)+(14x-20)+(x+3)=180 | | 8x^2+18x+74 | | -4-(-x)=17 | | 2(x+3)-4=5x+5 | | 3+k=25 | | 1 | | p+18=11 | | .6x^2=1.2x+.6 | | 2(6d+3)=18-3(16+-3d) | | 6x^2=12x+6 | | -4=-18+p | | 4x^2-4x-3= | | 2a-(3b+a)-b | | 1g+4-3G=1+g | | -5=-5(3d-8) | | 9x+10=5x+2 | | 3+648x^3 | | 2x+x+3=6x | | -96=4(2x-8) |

Equations solver categories